Sigap Kaki DM Innovation: Comprehensive Early Detection and Self-Education For Diabetic Foot Ulcer Prevention: Inovasi Sigap Kaki DM (Siaga Kaki Diabetes Mellitus): Deteksi Dini Komprehensif dan Edukasi Mandiri untuk Pencegahan Ulkus Kaki Diabetes - Dekcy Vrista Tri Anggoro; Badrul Nurul Hisyam; Harsah Bahtiar Zainudin; Ahmad Rifai; Wisnu Widodo Eko Putra (KHD Production, 2025)
Diabetes mellitus (DM) is a chronic metabolic disease with an increasing global prevalence. One of its most serious complications is diabetic foot ulcer (DFU), which often leads to infection, lower limb amputation, and decreased quality of life. Primary healthcare plays a vital role in early detection and prevention of DFU. This community service aimed to develop and implement the innovation “SIGAP KAKI DM” (Comprehensive Early Detection and Self-Education for Diabetic Foot Ulcer Prevention) at Puskesmas Panti, Jember. The program was designed to improve the knowledge and skills of healthcare workers in diabetic foot screening and patient education. Thirteen healthcare workers participated in interactive training sessions, consisting of lectures on DFU risk factors, demonstrations of foot examination techniques, and hands-on practice using monofilaments, tuning forks, and ankle-brachial index (ABI) measurement. Pretest and posttest evaluations showed a significant increase in participants’ knowledge and skills, with “good” scores improving from 23.1% to 92.3%. Healthcare workers were able to perform diabetic foot examinations independently and educate patients on self-care practices. Educational materials such as booklets and posters were also developed to support patient empowerment in foot care. The innovation has potential to be integrated into routine services at primary healthcare centers to prevent DFU and reduce amputation rates among DM patients. Sustained implementation and cross-sector collaboration are recommended to ensure program effectiveness and long-term impact.